Caecal worm, Aulonocephalus pennula, infection in the northern bobwhite quail, Colinus virginianus. Issue 1 (April 2017) - Dunham, Nicholas R.; Henry, Cassandra; Brym, Matthew; Rollins, Dale; Helman, R. Gayman; Kendall, Ronald J.
Abstract: Parasitic nematodes that infect quail have been understudied and long been dismissed as a problem in quail management. Within the Rolling Plains ecoregion of Texas, an area that has experienced quail population "boom and bust" cycles and ultimately a general decline, the need to determine why Northern bobwhite ( Colinus virginianus ) populations are diminishing has increased in priority. Previously, caecal parasites have been documented to cause inactivity, weight loss, reduced growth, inflammation to the caecal mucosa, and even death. The caecal worm Aulonocephalus pennula is an intestinal nematode parasite that is commonly found within the caecum of quail, as well as many other avian species. In the Rolling Plains ecoregion, A. pennula has been documented to have as high as a 98% prevalence in bobwhite quail samples; however, the effect it has on its host is not well understood. The present study documents A. pennula causes no pathological changes within the caeca of the Northern bobwhite. However, there is concern for disruption of digestion and the possible implications of infection for wild bobwhite quail survival are discussed. Graphical abstract: Highlights: A. pennula found in all samples. No significant changes in the caecal wall in infected bobwhites. Minimal digesta found in A. pennula infection bobwhites.